2020
DOI: 10.1159/000511101
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Cherry Angiomas and Skin Melanoma: Further Insights into an Intriguing Association

Abstract: <b><i>Background:</i></b> Some risk factors for malignant melanoma (MM) are recognized. <b><i>Objective:</i></b> To compare the strength of association between MM and eruptive cherry angiomas (CAs) with that of other well-known associations. <b><i>Methods:</i></b> This cross-sectional study included all subjects referred to the Outpatient Dermatology-Oncology and Dermoscopy Units of the Universities of Ferrara and Bologna, Italy, over a 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…The aetiology of eCAs has not been fully elucidated but chemicals, immunosuppression, chronic graft‐versus‐host disease, lymphoproliferative diseases, human herpesvirus‐8 infection and downregulation of microRNA‐424 have been considered as potential inducers or predisposing factors for the development of CAs 2 . We found that more than half of our patients with UM had eCA, which is higher than the global population prevalence (range 41%–48%) 4 …”
Section: Ecas (N = 21) No Ecas (N = 12) or 95% CI P Total Group N % N % N %mentioning
confidence: 69%
See 4 more Smart Citations
“…The aetiology of eCAs has not been fully elucidated but chemicals, immunosuppression, chronic graft‐versus‐host disease, lymphoproliferative diseases, human herpesvirus‐8 infection and downregulation of microRNA‐424 have been considered as potential inducers or predisposing factors for the development of CAs 2 . We found that more than half of our patients with UM had eCA, which is higher than the global population prevalence (range 41%–48%) 4 …”
Section: Ecas (N = 21) No Ecas (N = 12) or 95% CI P Total Group N % N % N %mentioning
confidence: 69%
“…The onset of eCAs is typically 40–50 years of age and they tend to increase in number and size with time, 2 which could explain the relatively high incidence of eCAs in our UM sample. Patients with UM and eCAs were slightly younger than patients with UM without eCAs; this association might be spurious, or it might suggest a potential association between the two lesions.…”
Section: Ecas (N = 21) No Ecas (N = 12) or 95% CI P Total Group N % N % N %mentioning
confidence: 94%
See 3 more Smart Citations